INFORMOLOGY AND METHODOLOGY EDUCATION IN PEDAGOGICAL UNIVERSITY - Shakotko, Viktor (Continuing Professional Education: Theory and Practice, 2019)
The necessity of improving the training process of future teachers of informatics due to the fundamentalization of the training content, formation of IT-teachers informological competences system is substantiated. It is proposed to solve these tasks by introducing the discipline «Fundamentals of informology and methods of teaching basic concepts of informology in secondary school» into the system of IT – teachers’ training and professional development, which will allow generalizing and systematizing the knowledge of basic concepts of informatics. Teaching informology is a component of theoretical and, consequently, professional training of future IT-teachers, fundamentalization of their professional training content. At the same time, the investigation carried out on the development and implementation of methodological systems for the training of future informatics teachers shows that insufficient attention to the problems of the formation of informological competencies is paid. There is practically no scientific work in which problems of informological competencies formation of future and active IT-teachers are thoroughly investigated. As the educational discipline «Informology» is absent in the curricula of the specialty «014 Secondary Education. Informatics» and other specialties, which are implemented by educational programs for the IT-teachers’ training. The article describes main components of the methodical system of informological competencies formation of future informatics teachers, which are realized during the course «Fundamentals of informology and methods of teaching basic concepts of informology in secondary school». The purpose and content of training are substantiated; forms, methods and means that can be used in the process of specified course training are described.